2006
DOI: 10.1007/s10681-006-9229-x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of resistance to the chlorosis component of tan spot of wheat caused by Pyrenophora tritici-repentis, races 1 and 3

Abstract: The fungus Pyrenophora tritici-repentis, causal agent of tan spot of wheat, produces two phenotypically distinct symptoms, tan necrosis and extensive chlorosis. The inheritance of resistance to chlorosis induced by P. tritici-repentis races 1 and 3 was studied in crosses between common wheat resistant genotypes Erik, Hadden, Red Chief, Glenlea, and 86ISMN 2137 and susceptible genotype 6B-365. Plants were inoculated under controlled environmental conditions at the two-leaf stage and disease rating was based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Tsc1 and Tsc2 genes ( Tan spot chlorosis ) sensitive for ToxC and ToxB ( Ciuffetti et al., 2014 ). Furthermore, several more genes have been recognized through conidial inoculations which are not associated with HSTs and have been named as ‘Tsr’ (Tan spot resistance) ( Singh and Hughes, 2006 ; Tadesse et al., 2006a ; Tadesse et al., 2006b ; McIntosh and Yamazaki, 2008 ; Singh et al., 2008 ). Toxin sensitivity was shown to be controlled by the Tsn1 gene ( Lamari and Bernier, 1989b ; Faris et al., 1996 ).…”
Section: Selected Fungal Pathogens On Grassesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsc1 and Tsc2 genes ( Tan spot chlorosis ) sensitive for ToxC and ToxB ( Ciuffetti et al., 2014 ). Furthermore, several more genes have been recognized through conidial inoculations which are not associated with HSTs and have been named as ‘Tsr’ (Tan spot resistance) ( Singh and Hughes, 2006 ; Tadesse et al., 2006a ; Tadesse et al., 2006b ; McIntosh and Yamazaki, 2008 ; Singh et al., 2008 ). Toxin sensitivity was shown to be controlled by the Tsn1 gene ( Lamari and Bernier, 1989b ; Faris et al., 1996 ).…”
Section: Selected Fungal Pathogens On Grassesmentioning
confidence: 99%
“…Tsc1 and Tsc2 genes (Tan spot chlorosis) sensitive for ToxC and ToxB (Ciuffetti et al, 2014). Furthermore, several more genes have been recognized through conidial inoculations which are not associated with HSTs and have been named as 'Tsr' (Tan spot resistance) (Singh and Hughes, 2006;Tadesse et al, 2006a;Tadesse et al, 2006b;McIntosh and Yamazaki, 2008;Singh et al, 2008). Toxin (Lamari et al, 1995;Lamari et al, 1998;Ali and Francl, 2003;Singh, 2007;Aboukhaddour et al, 2013) and the Southern Cone Region of South America (Singh, 2007) Race 3 ToxC 3 North America (Lamari et al, 1998;Ali and Francl, 2003;Singh, 2007;Aboukhaddour et al, 2013) and the Caucasus region (Lamari et al, 2005) Race 4 No HTSs 4 North America (Lamari et al, 1995;Lamari et al, 1998;Ali and Francl, 2003;Singh, 2007;Aboukhaddour et al, 2013) and North Africa (Benslimane et al, 2011) Race 5…”
Section: Pyrenophora Tritici-repentismentioning
confidence: 99%
“…Genetic analysis of wheat- P. tritici-repentis interactions have revealed that host resistance ranges from qualitative [10,11,12,13,14] to quantitative control [15,16,17,18,19,20]. Some studies utilizing quantitative trait loci (QTL) analysis reported resistance to TS as polygenic, but observed that previously reported major genes frequently underline these QTLs [18,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The mode of inheritance of resistance to chlorosis also varied from recessive, through partially dominant to dominant depending upon the parental genotypes (Singh and Hughes 2006b). Moreover, the expression of tan spot chlorotic symptom is continuous and highly influenced by environment (Singh and Hughes 2006b). The germplasm used in this study showed contrasting high levels of resistance and susceptibility and discrete differences in reaction permitted a showing the location of gene Tsr1 for resistance to tan spot and insensitivity to culture filtrate of Pyrenophora tritici-repentis race 2.…”
Section: Disease Score Ril Frequencymentioning
confidence: 90%
“…However, Singh et al (2008a) observed that resistance to race 5 was controlled by a single dominant gene whereas Friesen and Faris (2004) reported resistance to be quantitative with the toxin-insensitivity gene, Tsc2, mapping to the distal region of chromosome 2BS accounting for 69% of the phenotypic variation. The mode of inheritance of resistance to chlorosis also varied from recessive, through partially dominant to dominant depending upon the parental genotypes (Singh and Hughes 2006b). Moreover, the expression of tan spot chlorotic symptom is continuous and highly influenced by environment (Singh and Hughes 2006b).…”
Section: Disease Score Ril Frequencymentioning
confidence: 99%